Technical Services in the Electronic Information Environment - Satija, M.P. (DESIDOC Journal of Library & Information Technology, 2003)
Technical services are as a mix of skilled and professional jobs (done mostly behind the screen) to provide user services in libraries. Technical services have been with the libraries throughout their evolution from the days of clay tablets, papyrus to paper and virtual libraries. Technical services have evolved making use of available technology of the day. In the days of all powerful and era-defining information technology, the technical services are still necessary to help libraries to accomplish their mission of connecting users with the needed information. New technology affords splendid opportunity to extend and augment intensively and improve qualitatively the library services to the users. OPACs not only haw tremendous capacity but equally versatile powerful searching capabilities and mechanism. Classification has many new roles to play in designing, searching and managing electronic databases. This paper cites Electronic Dewey as an example to illustrate the role of IT in editing and publishing classification schedules. At the end some unsolved issues have been identified and emerging trends in technical services are enumerated. http://dx.doi.org/10.14429/dbit.19.3.3485